Controls on fluvial sedimentary architecture and sediment‐fill state in salt‐walled mini‐basins: Triassic Moenkopi Formation, Salt Anticline Region, SE Utah, USA. (25th May 2013) - Banham, Steven G.; Mountney, Nigel P.
Abstract The Triassic Moenkopi Formation in the Salt Anticline Region, SE Utah, represents the preserved record of a low‐relief ephemeral fluvial system that accumulated in a series of actively subsiding salt‐walled mini‐basins. Development and evolution of the fluvial system and its resultant preserved architecture was controlled by the following: (1) the inherited state of the basin geometry at the time of commencement of sedimentation; (2) the rate of sediment delivery to the developing basins; (3) the orientation of fluvial pathways relative to the salt walls that bounded the basins; (4) spatially and temporally variable rates and styles of mini‐basin subsidence and associated salt‐wall uplift; and (5) temporal changes in regional climate. Detailed outcrop‐based tectono‐stratigraphic analyses demonstrate how three coevally developing mini‐basins and their intervening salt walls evolved in response to progressive sediment loading of a succession of Pennsylvanian salt (the Paradox Formation) by the younger Moenkopi Formation, deposits of which record a dryland fluvial system in which flow was primarily directed parallel to a series of elongate salt walls. In some mini‐basins, fluvial channel elements are stacked vertically within and along the central basin axes, in response to preferential salt withdrawal and resulting subsidence. In other basins, rim synclines have developed adjacent to bounding salt walls and these served as loci for accumulation of stacked fluvial channel complexes. Neighbouring mini‐basins exhibit different styles of infill at equivalent stratigraphic levels: sand‐poor basins dominated by fine‐grained, sheet‐like sandstone fluvial elements, which are representative of nonchannelised flow processes, apparently developed synchronously with neighbouring sand‐prone basins dominated by major fluvial channel‐belts, demonstrating effective partitioning of sediment route‐ways by surface topography generated by uplifting salt walls. Reworked gypsum clasts present in parts of the stratigraphy demonstrate the subaerial exposure of some salt walls, and their partial erosion and reworking into the fill of adjoining mini‐basins during accumulation of the Moenkopi Formation. Complex spatial changes in preserved stratigraphic thickness of four members in the Moenkopi Formation, both within and between mini‐basins, demonstrates a complex relationship between the location and timing of subsidence and the infill of the generated accommodation by fluvial processes.